Dampak Perputaran Harga Cabai terhadap Pendapatan Kelompok Tani Fajar Amanas Desa Biau Kecamatan Io Kufeu Kabupaten Malaka - Erwindus H Nurak; Fransina W. Ballo; Cicilia A. Tungga (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to describe the impact of chili price volatility on the income of Fajar Amanas Farmers Group, Biau Village, Io Kufeu District, Malaka Regency. The research method used is a qualitative descriptive method and its implementation uses interview and documentation techniques. The research location chosen is the Fajar Amanas Farmers Group located in Biau Village, Io Kufeu District, Malaka Regency, East Nusa Tenggara Province. The types of data used are primary and secondary data. The results of the study showed that the total cost of chili cultivation was Rp6,776,000 with a total production per month of 200 kilograms, with a total price of Rp100,000 per kilogram, the total income was Rp20,000,000, with a total income of Rp13,224,000.